PENGEMBANGAN INSTRUMEN LIFE SKILLS SISWA - Normawati Normawati (Jurnal Evaluasi Pendidikan, 2016)
The aim of this research is to develop students’ life skills instruments. Measurement instrument of students’ life skills is a set of non-test self assessment instrument (self-report) using Likert scale. The sample of the study was taken by multistage random sampling method. The construct of life skills consists of five dimensions, namely: personal skills of self-awareness, personal skills of rational thinking, social skills, academic skills, and vocational skills. From the study to the experts and panelists, 67 items selected to be used which its’ interrater reliability coefficient values above 0.8. The instrument is tested twice to high school students of class XI, each 335 students as testee. Empirically, by testing the confirmatory factor analysis obtained loading factor value above 0.3 and the value of t over 1.96. From the calculation of the value of multidimensional reliability coefficient indicates that the value of Construct Reliability (CR) of more than 0.9 and the value of Variance Extracted (VE) is greater than 0.6, which means the level of validity and reliability of life skills assessment instruments of high school students is high. It can be concluded that the construct validity and reliability of life skills assessment instrument are good.